The Dark side of family communication - Olson, Loreen N.; Baiocchi-Wagner, Elizabeth A.; Kratzer, Jessica M. W.; Symonds LeBlanc, Sarah E. (Cambridge, England ; Malden, MA : Polity Press, 2012)
"This text provides for the first time in book form an exploration of the communicative aspects of the darker side of family life, ranging from, for example, severe acts of violence to more subtle forms of conflict. In addition to offering a working definition of the concept of the 'dark side' in the family context, the authors propose the Darkness Model of Family Communication that integrates relevant literature in new and significant ways."--p. 4 of cover
Prologue -- Conceptualizing the "dark side" of family communication -- Individual influence on the darkness of family communication -- 3. The dark side of dyadic family life -- Familial interaction structure and the dark side -- Dark family communication in a context of darkness -- Concluding thoughts -- References -- Index.
Includes bibliographical references and indexes.
Keywords: Communication in families; Dysfunctional families